Revisiting Female Resilience within the Psychiatric in Janice Galloway’s Fiction - González Sampedro, Irene (Complutense Journal of English Studies, 2021)
The aim of this article is to analyse the fractures in the performance of normative discourses of identity in Janice Galloway’s novel The Trick Is To Keep Breathing (1989) and her short story “and drugs and rock and roll”, included in her latest collection Jellyfish (2015). Drawing on the thematic dialogue between the two works, set in Scotland, this article focuses specifically on their protagonists’ processes of healing following a period of depression, and the urban spatial representation of these experiences. In order to do so, it examines various practices associated with psychiatrics that isolate and dehumanise citizens and lead to the creation of a sharp social dichotomy as regards wellbeing. Finally, the article approaches the spatial embodiment of these characters, as well as the creation of alternative spaces inside medical institutions as part of a continuum in Galloway’s exploration of female resilience.